In Silico Study of Flavonoid from Caesalpinia sappan L. against HMG-CoA Reductase as Antihypercholesterolemia - Luhung, Aditya; Shefelin, Kinar; Adiputri, Nurqisthi Iqlima; Deliyana, Alifa Nisa; Colin, Michelle Natasha; Claudina, Nur Shelly Ester; Nuwarda, Rina Fajri (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
Hypercholesterolemia is a severe condition characterized by elevated blood cholesterol levels exceeding 240 mg/dL, contributing to over 18.5 million deaths since 2019. Simvastatin, a widely used cholesterol-lowering therapy, inhibits the enzyme HMG-CoA reductase. However, despite its efficacy, statin-based drugs can cause adverse effects such as hepatotoxicity, malaise, rhabdomyolysis, and myopathy. Sappan wood (Caesalpinia sappan L.) is a potential alternative known for its antihypercholesterolemic properties, attributed to its main compounds: sappanone B, brazilin, and hematoxylin. This study aimed to evaluate the potential of flavonoids in sappan wood as HMG-CoA reductase inhibitors using molecular docking analysis. The results revealed that sappanone B exhibited the lowest binding energy (-7.71 kcal/mol) and an inhibition constant of 2.22 μM, followed by brazilin (-7.34 kcal/mol, 4.17 μM) and hematoxylin (-7.00 kcal/mol, 7.45 μM). These findings suggest that sappanone B, brazilin, and hematoxylin possess significant potential as competitive HMG-CoA reductase inhibitors, providing a promising natural alternative for hypercholesterolemia treatment with potentially fewer side effects.